Applicability evaluation of multiple sets of soil moisture data on the tibetan plateau - Dong, Xuefeng; Lai, Xin; Wang, Yingsi; Dong, Wei; Zhu, Jun; Dong, Li; Cen, Sixian (Frontiers in Earth Science, 2022)
Based on the in-situ data of the soil moisture observing networks established at the Maqu, Naqu, Ali, and Shiquanhe (Sq) in the Tibetan Plateau (TP), using five evaluation indices: the Pearson correlation coefficient (R), root mean square error (RMSE), mean deviation (bias), standard deviation ratio (SDV) and unbiased RMSE (ubRMSE)，the applicability of the COMBINED, ACTIVE, PASSIVE, ERA5, ERA5-Land (LAND), ERA-Interim (INTERIM), CLSM and NOAH soil moisture datasets was comprehensively evaluated. The results showed that, at the observation networks scale, the ACTIVE product exhibited the best applicability in Maqu (R = 0.704, ubRMSE = 0.040 m3/m3); the COMBINED product performed best in Naqu (R = 0.803, bias = 0.016 m3/m3); the LAND data displayed the best consistency in Ali observations (R = 0.734, bias = -0.035 m3/m3); and the ERA5 data not only showed the best performance in the Sq area (R = 0.793, bias = -0.037 m3/m3) but also exhibited good results in the other three observation networks (R > 0.6). In the Maqu small-scale evaluation, the ACTIVE product performed best, followed by the ERA5 data. The COMBINED and PASSIVE products had serious gaps in the Ali and Sq areas, and had the worst applicability on the western TP. ERA5 was the most suitable soil moisture dataset for the TP considering the correlation results and temporal and spatial continuity.